Elucidating the Synergic Effect in Nanoscale MoS2/TiO2 Heterointerface for Na‐Ion Storage. Issue 35 (30th October 2022) - Ma, Chunrong; Hou, Dewen; Jiang, Jiali; Fan, Yanchen; Li, Xiang; Li, Tianyi; Ma, Zifeng; Ben, Haoxi; Xiong, Hui
Abstract: Interface engineering in electrode materials is an attractive strategy for enhancing charge storage, enabling fast kinetics, and improving cycling stability for energy storage systems. Nevertheless, the performance improvement is usually ambiguously ascribed to the "synergetic effect", the fundamental understanding toward the effect of the interface at molecular level in composite materials remains elusive. In this work, a well‐defined nanoscale MoS2 /TiO2 interface is rationally designed by immobilizing TiO2 nanocrystals on MoS2 nanosheets. The role of heterostructure interface between TiO2 and MoS2 by operando synchrotron X‐ray diffraction (sXRD), solid‐state nuclear magnetic resonance, and density functional theory calculations is investigated. It is found that the existence of a hetero‐interfacial electric field can promote charge transfer kinetics. Based on operando sXRD, it is revealed that the heterostructure follows a solid‐solution reaction mechanism with small volume changes during cycling. As such, the electrode demonstrates ultrafast Na + ions storage of 300 mAh g −1 at 10 A g −1 and excellent reversible capacity of 540 mAh g −1 at 0.2 A g −1 . This work provides significant insights into understanding of heterostructure interface at molecular level, which suggests new strategies for creating unconventional nanocomposite electrode materials for energy storage systems. Abstract : The heterointerfaces play an important role in providing additional active sites for enhanced charge storage as well as give rise to pseudocapacitive behavior with suppressed phase transitions for fast kinetics. The built‐in electrical field could reduce the diffusion barrier to strengthen the ion diffusion and charge transfer.